Rotational multi-beam energy harvester with up-conversion mechanism in an extremely low frequency scenario. (1st April 2022) - Febbo, M.; Machado, S.P.
Graphical abstract: The rectified power overcomes 6.4 times in average other previous designs. Highlights: A multi-beam rotational energy harvester is presented and modelled. Two frequency-up conversion mechanisms, improve the harvested energy. A sizeable mass impacts the top beam providing a large voltage output. An impact stop avoids large incursions of the beams. A piezoelectric buzzer replaces the impact stop providing additional energy. A harvested DC power of 23–150 μW for 0.8–2.2 Hz over a 10 K resistor is collected. Abstract: We propose a novel frequency-up converting device in an extremely low frequency rotating scenario based on a multi-beam piezoelectric energy harvester and multiple impacts. The rotating multi-beam structure consists of a piezoelectric sheet added to a top beam, a large seismic mass added to a bottom beam and an elastic stop which can be eventually replaced by a buzzer. At half of the rotating cycle, the bottom beam impacts the top beam by means of a spring generating energy by a frequency up-conversion mechanism. At the other half of the cycle, the up and bottom beam separate from each other and the bottom beam impacts an elastic stop or a buzzer which are used to simultaneously recover the kinetic energy of the collision, generate energy (buzzer) and prevent possible damage to the structure. An analytical model that governs the electromechanical equations and the impact dynamics is proposed to provide a means to predict the generated output energy. The model is based on the Euler-Bernoulli structural theory for the beams and a piezoelectric nonlinear constitutive model. Two different energy generation possibilities are studied, depending on the selection of the elastic stop or the buzzer. When the elastic spring acts as stop, the collision between the bottom beam and the stop is more elastic. Replacing the spring stop with a piezo buzzer adds to the system an additional mechanism of energy conversion. By making several experimental tests, the analytical model is validated by computing the cumulated energy. The results demonstrate that the buzzer element significantly improves the harvested power when it replaces the elastic stop. To estimate the usable power of the device, rectifier circuits coupled to the piezo elements are built and test. The results show that in the case of the buzzer used as a stop, a rectified power that overcomes 6.4 times in average other previous designs is harvested in the range of 0.8–2.2 Hz over an electrical load of 10 kΩ. The amount of collected power is suitable for autonomous sensing of wind turbines of 30 kW with rotational speeds of between 50 and 150 rpm.